2019
DOI: 10.1002/advs.201900752
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Changes in Patients with Bipolar Depression

Abstract: This study aims to characterize the gut microbiota in depressed patients with bipolar disorder (BD) compared with healthy controls (HCs), to examine the effects of quetiapine treatment on the microbiota, and to explore the potential of microbiota as a biomarker for BD diagnosis and treatment outcome. Analysis of 16S‐ribosomal RNA gene sequences reveals that gut microbial composition and diversity are significantly different between BD patients and HCs. Phylum Bacteroidetes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
174
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 120 publications
(185 citation statements)
references
References 67 publications
(96 reference statements)
10
174
0
1
Order By: Relevance
“…In terms of BD, previous studies found that BD was mainly associated with disturbances of Firmicutes and Bacteroidetes phyla . Consistent with this finding, we found that Firmicutes, Bacteroidetes, and Proteobacteria phyla were altered in BD relative to HC.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In terms of BD, previous studies found that BD was mainly associated with disturbances of Firmicutes and Bacteroidetes phyla . Consistent with this finding, we found that Firmicutes, Bacteroidetes, and Proteobacteria phyla were altered in BD relative to HC.…”
Section: Discussionsupporting
confidence: 90%
“…Herein, we found that the indices of α‐diversity (Ace and Chao) were decreased in BD relative to HC. Supporting this finding, lower gut microbial indices of α‐diversity (Chao and Obs) were also observed in a previous smaller sample size study of just BD versus HC . Moreover, both this current and our previous studies found no α‐diversity differences between MDD and HC.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations